2019
DOI: 10.1186/s12871-019-0851-2
|View full text |Cite
|
Sign up to set email alerts
|

Regional versus systemic analgesia in video-assisted thoracoscopic lobectomy: a retrospective analysis

Abstract: BackgroundThe optimal perioperative analgesic strategy in video-assisted thoracic surgery (VATS) for anatomic lung resections remains an open issue. Regional analgesic concepts as thoracic paravertebral or epidural analgesia were used as systemic opioid application. We hypothesized that regional anesthesia would provide improved analgesia compared to systemic analgesia with parenteral opioids in VATS lobectomy and would be associated with a lower incidence of pulmonary complications.MethodsThe study was approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…There was not a significant difference in pain levels between these groups in our study (Table IV). Our study revealed that lung resections with uniportal incisions result in lower pain scores and pain control was comparable with systemic or epidural pain control methods in accordance with the reported experiences of different clinics in the literature [19,20]. We compared the patients in 2 groups according to the size of resection: named as wedge resection and anatomical resection.…”
Section: Discussionsupporting
confidence: 83%
“…There was not a significant difference in pain levels between these groups in our study (Table IV). Our study revealed that lung resections with uniportal incisions result in lower pain scores and pain control was comparable with systemic or epidural pain control methods in accordance with the reported experiences of different clinics in the literature [19,20]. We compared the patients in 2 groups according to the size of resection: named as wedge resection and anatomical resection.…”
Section: Discussionsupporting
confidence: 83%
“…Along with physical rehabilitation, postoperative pain management plays a key role in achieving the rapid improvement of lung function (83,84). Effective postoperative analgesic measures can promote early diaphragmatic movement, coughing, and expectoration, thereby reducing damage to lung function and decreasing pulmonary infections (85).…”
Section: Rational Use Of Analgesicsmentioning
confidence: 99%
“…Epidurals have been used for VATS surgery. However, the lesser surgical trauma and less intense postoperative pain compared to thoracotomy, the potential for significant side effects associated with thoracic epidural catheterization and the availability of effective, simpler regional analgesia blocks make the use of epidural analgesia questionable in this context (18)(19)(20). However, epidural placement may be considered when there is a high probability of conversion to open thoracotomy.…”
Section: Optimal Postoperative Thoracic Analgesia After Vats Remains An Open Issuementioning
confidence: 99%